The investigation of parameters affecting boron removal by electrocoagulation method - Yilmaz, AE; Boncukcuoglu, R; Kocakerim, MM; Keskinler, B (Elsevier, 2005)
Boron removal from wastewaters by electrocoagulation using aluminum electrode material was investigated in this paper. Several working parameters, such as pH, current density, boron concentration and type and concentration of supporting electrolyte were studied in an attempt to achieve a higher removal capacity. The experiments were carried out by keeping the pH of solution constant and optimum pH of solution was determined 8.0 for the aluminum electrode. Although energy consumption increased with decreasing boron concentration, which conductivity of these solutions were low, boron removal efficiency was higher at 100 mg/L than that of 1000 mg/L. Current density was an important parameter affecting removal efficiency. Boron removal efficiency and energy consumption increased with increasing current density from 1.2 to 6.0 mA/cm(2). The types of different supporting electrolyte were experimented in order to investigate to this parameter effect on boron removal. The highest boron removal efficiency, 97%, was found by CaCl2 Added CaCl2 increased more the conductivity of solution according to other supporting electrolytes, but decreased energy consumption. The results showed to have a high effectiveness of the electrocoagulation method in removing boron from aqueous solutions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: electrocoagulation; boron removal; aluminum electrode; pH; wastewater treatment